Anthocyanin concentration depends on the counterbalance between its synthesis and degradation in plum fruit at high temperature - Junping Niu (Nature Portfolio, 2017)
Abstract Anthocyanin synthesis and degradation processes were analyzed at transcript, enzyme, and metabolite levels to clarify the effects of high temperature on the concentration of anthocyanin in plum fruit (Prunus salicina Lindl.). The transcript levels of PsPAL, PsCHS, and PsDFR decreased while those of PsANS and PsUFGT were similar at 35 °C compared with 20 °C. The activities of the enzymes encoded by these genes were all increased in fruits at 35 °C. The concentrations of anthocyanins were higher at 35 °C on day 5 but then decreased to lower values on day 9 compared with that at 20 °C. Furthermore, high temperature (35 °C) increased the concentration of hydrogen peroxide and the activity of class III peroxidase in the fruit. The concentration of procatechuic acid, a product of the reaction between anthocyanin and hydrogen peroxide, hardly changed at 20 °C but was significantly increased at 35 °C on day 9, indicating that anthocyanin was degraded by hydrogen peroxide, which was catalyzed by class III peroxidase. Based on mathematical modeling, it was estimated that more than 60–70% was enzymatically degraded on day 9 when the temperature increased from 20 °C to 35 °C. We conclude that at the high temperature, the anthocyanin content in plum fruit depend on the counterbalance between its synthesis and degradation.